Aberrant in physicochemical properties, functional health and medicinal grades of honeys from different sales outlets in Southwest Nigeria - Akinwande, Kayode Lawrence (2023)
The moisture content of the honey within and between the groups was significantly different (p < 0.05). Moisture content values that fall below and above the CAC standard range of 16.4–20.0% were recorded for 7(46.67%) and 5(33.33%) samples from the local honey parkers (HL) and supermarkets (HS), respectively (Table 4). The average moisture content for honey sampled from the beekeepers (HB) and supermarkets was significantly related. There was no significant difference in values within and between the group of the honey samples from the three sources. The pH values of all the honey samples are within 3.2–4.5 (CAC). The honey samples from the beekeepers have ash contents values of 0.25–1.0 in line with CAC and IHC, whereas 7 (46.66%) and 2 (13.33%) (Table 4) of honey samples from the supermarkets and local handlers/parkers, respectively, deviated from this standard values.